Does Angiotensin II Peak in Response to SARS-CoV-2? - Xavier, Léder Leal; Neves, Paula Fernanda Ribas; Paz, Lisiê Valeria; Neves, Laura Tartari; Bagatini, Pamela Brambilla; Timmers, Luís Fernando Saraiva Macedo; Rasia-Filho, Alberto Antônio; Mestriner, Régis Gemerasca; Wieck, Andrea (Frontiers in Immunology, 2021)
Human infection by the SARS-CoV-2 is causing the current COVID-19 pandemic. With the growing numbers of cases and deaths, there is an urgent need to explore pathophysiological hypotheses in an attempt to better understand the factors determining the course of the disease. Here, we hypothesize that COVID-19 severity and its symptoms could be related to transmembrane and soluble Angiotensin-converting enzyme 2 (tACE2 and sACE2); Angiotensin II (ANG II); Angiotensin 1-7 (ANG 1-7) and angiotensin receptor 1 (AT1R) activation levels. Additionally, we hypothesize that an early peak in ANG II and ADAM-17 might represent a physiological attempt to reduce viral infection via tACE2. This viewpoint presents: 1) a brief introduction regarding the renin-angiotensin-aldosterone system (RAAS), detailing its receptors, molecular synthesis and degradation routes; 2) a description of the proposed early changes in the RAAS in response to SARS-CoV-2 infection, including biological scenarios for the best and worst prognoses; and 3) the physiological pathways and reasoning for changes in the RAAS following SARS-CoV-2 infection.